Lietuvių bendrinės kalbos balsių diferencinių požymių hierarchija - Pakerys, Antanas (Kalbotyra, 1975)
The paper deals with the problem of hierarchical structure of the Lithuanian vowel system. The present study is based on the psychoacoustical data obtained in our earlier research. The algorithm of hierarchical clustering worked out by S. Johnson was applied.All obtained psychoacoustical groups of the Lithuanian vowels are found to coincide exactly with the groups of vowels distinguished at the phonological level. According to the hierarchy of psychoacoustical groups the distinctive features are to be ordered as follows: 1) tonality, 2) compactness, 3) diffuseness, 4) tenseness. This hierarchical structure is in good agreement with the articulatory triangle (trapezium) of vowels.